Ghana: Joint sector review assessment: Advancing mutual accountability through comprehensive, inclusive, and technically robust review and dialogue - Ministry of Food and Agriculture, Ghana (Government of Ghana, Ministry of Food and Agriculture, 2014)
In any sector, policy dialogue is a critical component to efficient and harmonious policymaking and implementation. A joint sector review (JSR) is an annual review of the sector to identify where challenges are preventing coherent dialogue. In Ghana, the first agriculture JSR was instituted in 2008 with the goal of reaching a common point-of-view among key sector stakeholders on important achievements in the preceding year. Stakeholders include the Ministry of Food and Agriculture (MoFA); development partners (DPs); other ministries, departments, and agencies (MDAs), the private sector, and civil society. In addition, the JSR seeks to review key remaining implementation challenges in the sector; assesses progress against strategic reform priorities and toward expected outputs and outcomes; and develop clear recommendations to prioritize reforms that feed into medium-term planning and budgeting exercises. This can be achieved through a sector-wide stakeholder meeting and consultation.